ISLAMIC EDUCATION IN PAKISTAN AND ITS OBJECTIVES FOR PEACEFUL SOCIETY: ANALYTICAL STUDY - Dr Asjad Ali; Dr Abdul Aleem; Dr Naseem Mahmood; Dr Maria Mann (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
One of Pakistan’s greatest challenges is a lack of opportunity for religious pluralism and secularism. One of Pakistan’s greatest challenges is the spread of Islamic doctrine across the country’s education system. The current state of affairs is the direct result of several policy initiatives undertaken by successive Pakistani governments dating back to the 1960s, beginning with the first military dictatorship. This article examines Pakistan’s education policy, constitutional and legislative laws, as well as the implications of the process of Islamization. The textbooks and instructional programs utilized by Pakistan’s various school districts are also examined in this research. In this study, it was concluded that the educational system in Pakistan aims to produce a Muslim rather than a global citizen who is able to think clearly and rationally. Paper given here concludes that the Pakistani educational system promotes intolerance and disregard for the country’s religious diversity. In addition, it promotes militancy and violence, as well as intolerance and discrimination towards one’s own countrymen.